Solid Variant of Aneurysmal Bone Cyst Masquerading as Malignancy - Ashok Singh; Abdul Majeed; Supriya Mallick; Shah Alam Khan; Asit Ranjan Mridha (Journal of Clinical and Diagnostic Research, 2017)
Solid Variant of Aneurysmal Bone Cyst (SVABC) is an uncommon neoplasm seen in young patients. The lesion presents clinically as well as on radiology like a malignant bone tumour. The aggressive features in most of the cases lead to a wrong diagnosis. Radiologically, it is expansile osteolytic with cortical breach being seen in many of the cases. We report two cases of SVABC which were misdiagnosed as malignant bone tumours. Both cases were seen in long bones. Radiologically both lesions were expansile, osteolytic, solid cystic, with destruction of cortex and were diagnosed as osteosarcomas. Both the cases were referred to us for further management and were subsequently diagnosed as SVABC. Being extremely rare these tumours have a high chance of getting misdiagnosed and knowledge of this entity along with close correlation with clinical, radiological and histopathological findings plays a critical role in accurately diagnosing this condition. An accurate diagnosis is of utmost importance as this changes the treatment drastically avoiding mutilating surgeries and unnecessary chemo radiotherapy.